The auditory brainstem response - Mochizuki, Y (No to hattatsu, 1989)
In 1967, Sohmer and Feinmesser recorded four negative peaks from extracochlear surface electrodes and they stated that the later components may be due to repetitive firing of auditory nerve fibers or may be due to the discharge of neurons in brain stem auditory nuclei. In 1970, Jewett, Romano and Williston presented the first full description of the scalp responses, postulated to be generated by brainstem nuclei. Since then, the auditory brainstem response (ABR) technique has attracted attention because it satisfied two previously unattainable needs; 1) a means of quantitative measurement of changes in auditory function in newborn babies or uncooperative patients, and 2) the detection of brainstem neurological abnormalities. Recording during wakefulness and in sleep or under drug intoxication has shown that ABRs are independent of the level of arousal or attention, and this feature is particularly useful for people unable to cooperate appropriately. Because of the close relationship to the anatomy of brainstem pathways, ABRs offer a neurophysiological index of neuronal function at the level of the brainstem. At present, these responses have become widely recognized as an important tool for the diagnosis of neurological diseases. One specific feature of the ABR is its dependence on maturation. The ABR appears at around 26 weeks of gestation and thereafter undergoes systematic changes in latency, amplitude and threshold. By using a supramaximal intensity of more than 60 dBHL, it is possible to evoke in all newborn babies with sufficient hearing ability, waves I, III and V.(ABSTRACT TRUNCATED AT 250 WORDS)